A proposta formativa do curso de gradua????o em letras: an??lise e discuss??o de seu desempenho a partir dos resultados do ENADE (2005-2014) - Desenzi, M??rcia Aparecida Monteiro (2019)
It is an exploratory bibliographic theoretical research, whose object is the Degree in Languages, based on the specific legislation and the documents of official bodies and educational institutions of the country, as well as research reports published by the literature on the area. Its purpose is to understand the precariousness of the undergraduate students training (Bachelor's and Teaching Degree in Portuguese, Spanish and English), as can be seen from the results of the students performance tests (ENADE), the ratings for courses and evaluation systems for education institutions promoted by education agencies (MEC - INEP) in recent years. Despite the incentives for development, the expansion of the public and private network, the access facilitation to higher education from the 1960s to the present, as well as the relaxation of the course structures and the Minimum Curriculum replacement with the Curricular Guidelines, undergraduate courses in Languages, including those aimed at foreign language teaching, had a significant quantitative increase, but continued to show a high qualitative deficit. The evaluation results of the National Exam of Student Performance (ENADE) from 2005 to 2014 show that the national averages for the students who are finishing these courses in higher education institutions throughout Brazil have grown little and reached very low levels, especially regarding the essay-questions skills. In the light of theoretical references based on a humanistic education conception in its formative role, this work questions the current curricular proposal of Language courses and offers suggestions for didactic and pedagogical strategies aiming raising quality of Licentiate and Bachelor???s classes in Languages.